Developments in the call centre industry: Analysis, changes and challenges - Julia Connell; John Burgess (Routledge, 2006)
Over the past ten years there has been a massive growth in call centres worldwide. These centres are said to represent the most dynamic growth area in white-collar employment internationally since the mid 1990s. Yet the footloose and global nature of the industry means that jobs will always be susceptible to outsourced operations, ICT developments, public sector subsidization of business restructuring and re-location, and cheaper operations elsewhere. This book conducts a thorough analysis of this modern phenomenon.
Keywords: 380; Telekommunikation; Telefon; Callcenter; Arbeitsbedingungen; Arbeitsorganisation; Welt